The Why, What, Who & How in business process outsourcing - Mitra, Protoya (2004)
Business Process Outsourcing (BPO) Industry has been growing at a phenomenal rate over the past 4-5 years. Companies started adopting this business model since this result in cost savings and allow the company to focus on its core competencies. Moreover there are specialists in the market who can manage the business function more efficiently than the company itself. Companies generally experience four basic decision making predicaments when they decide to go for outsourcing. Firstly they had to justify themselves why they are going for Outsourcing, secondly they have to decide on the Business Process to outsource, Thirdly they have to decide who can manage their business function in the most efficient manner and finally the most important part of it, how to manage the outsourcing deal. This study looks at all these aspects of decision making from the perspective of the clients as well as the service providers.